Development and Validation of Impurity Profiling and Stability Studies of Vericiguat using Ultra Performance Liquid Chromatography Method - Reehana Shaik, (Asian Journal of Pharmaceutics (AJP), 2025)
Background: To develop a stability-indicating, simple, accurate, and rapid reverse phase ultra-performance liquid chromatography (RP-UPLC) method for the detection and quantification of organic impurities in Vericiguat bulk drug, ensuring the safety of drug therapy through a selective analytical approach. Materials and Methods: Vericiguat bulk drug, along with its known impurities (impurity-1 [Imp-1] and impurity-2 [Imp-2]) were used. Simple and economical solvents and mobile phase components were employed in the ultra-performance liquid chromatography method. Linearity of the method was established over the concentration ranges of 37.5–225 μg/mL for Vericiguat, and 2.5–15 μg/mL for both Imp-1 and Imp-2, with a correlation coefficient (r2 ) of 0.999 for all analytes. Stress degradation studies were performed under various conditions to assess stability, particularly oxidative stress. Robustness was evaluated by deliberately varying method parameters. Recovery studies were conducted to assess accuracy and specificity in the presence of formulation excipients. Results: The developed method showed excellent resolution of impurities within a short run time. It was found to be robust and unaffected by small variations in method parameters. The stress testing revealed that Vericiguat is most sensitive to oxidative degradation, particularly in the presence of peroxide. Recovery results were consistent with label claims, with no interference from excipients. Conclusion: The developed RP-UPLC method is simple, fast, accurate, precise, robust, and economical. It is suitable for routine quality control analysis of Vericiguat and its impurities in bulk drug form.